Inferior gluteal artery perforator (IGAP) flap in autologous breast reconstruction: A proportional meta-analysis of surgical outcomes - Martineau Jérôme; Scampa Matteo; Viscardi Juan A.; Giordano Salvatore; Kalbermatten Daniel F.; Oranges Carlo M. (Churchill Livingstone, 2025)
Background: The inferior gluteal artery perforator (IGAP) flap is an alternative technique for autologous breast reconstruction. In contrast to other commonly used techniques, there is a paucity of literature on the safety and efficacy of the IGAP flap. The aim of this study was to perform a systematic literature review and meta-analysis of postoperative outcomes and complications associated with the IGAP in autologous breast reconstructions to validate its safety.
Methods: A systematic review of literature was performed following PRISMA guidelines. Articles reporting post-operative outcomes of IGAP flaps in autologous breast reconstruction were included. A proportional meta-analysis of post-operative complications was performed to obtain their proportions with 95% confidence intervals (CIs).
Results: Seven studies met the inclusion criteria, which represented a total of 239 IGAP flaps in 181 patients The total flap loss rate was 3% (95% CI 0-8%), partial flap loss rate was 2% (95% CI 0-4%), haematoma rate was 3% (95% CI 0-7%), overall donor-site complication rate was 15% (95% CI 5-28%), overall recipient-site complication rate was 24% (95% CI 15-34%), and the overall complication rate was 40% (95% CI 23-58%).
Conclusions: This meta-analysis provides comprehensive knowledge on the safety and efficacy of the IGAP flap in autologous breast reconstruction. It evidences the IGAP flap in autologous breast reconstruction's overall safety and validates its role as an effective option in breast reconstruction.